Improved serodiagnosis of cystic echinococcosis using the new recombinant 2B2t antigen. - Ana Hernández-González; Saúl Santivañez; Héctor H García; Silvia Rodríguez; Santiago Muñoz; Guillermo Ramos; Antonio Orduña; Mar Siles-Lucas (PLoS Neglected Tropical Diseases)
A standardized test for the serodiagnosis of human cystic echinococcosis (CE) is still needed, because of the low specificity and sensitivity of the currently available commercial tools and the lack of proper evaluation of the existing recombinant antigens. In a previous work, we defined the new ELISA-B2t diagnostic tool for the detection of specific IgGs in CE patients, which showed high sensitivity and specificity, and was useful in monitoring the clinical evolution of surgically treated CE patients. Nevertheless, this recombinant antigen gave rise to false-negative results in a percentage of CE patients. Therefore, in an attempt to improve its sensitivity, we constructed B2t-derived recombinant antigens with two, four and eight tandem repeat of B2t units, and tested them by ELISA on serum samples of CE patients and patients with related parasites. The best diagnostic values were obtained with the two tandem repeat 2B2t antigen. The influence of several clinical variables on the performance of the tests was also evaluated. Finally, the diagnostic performance of the 2B2t-ELISA was compared with that of an indirect haemagglutination commercial test. The 2B2t recombinant antigen performed better than the HF and B2t antigens, and the IHA commercial kit. Therefore, this new 2B2t-ELISA is a promising candidate test for the serodiagnosis of CE in clinical settings.